2020
DOI: 10.1055/s-0039-3402460
|View full text |Cite
|
Sign up to set email alerts
|

Pé diabético. Parte 2: Neuroartropatia de Charcot

Ricardo Cardenuto Ferreira

Abstract: ResumoA neuropatia de Charcot (NC) é uma complicação lamentável e comum de pacientes com diabetes, provavelmente resutlante de uma falta de entendimento adequado dessa condição, que leva ao diagnóstico tardio.A confusão diagnóstica com quadro infeccioso contribui para que o tratamento inicialmente indicado seja equivocado ao prescrever medicação antibiótica ou, eventualmente, drenagem cirúrgica. Não é infrequente que a drenagem inadvertida do suposto abcesso revele que na verdade seu conteúdo é formado apenas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(178 reference statements)
1
2
0
1
Order By: Relevance
“…Only 13% of patients were affected by DM1, whereas 47% of all patients required insulin therapy. These data are in line with the published data about this type of diabetic foot [8][9][10][11]. Additionally, Fede et al [26] demonstrated that in females, "the fascia becomes enriched in collagen-I, with low hormone levels, becoming more rigid during menopause".…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Only 13% of patients were affected by DM1, whereas 47% of all patients required insulin therapy. These data are in line with the published data about this type of diabetic foot [8][9][10][11]. Additionally, Fede et al [26] demonstrated that in females, "the fascia becomes enriched in collagen-I, with low hormone levels, becoming more rigid during menopause".…”
Section: Discussionsupporting
confidence: 87%
“…Charcot diabetic foot is a chronic complication with a unilateral onset that becomes bilateral over time, presenting a distinct evolution in two phases, acute and chronic [10]. The prevalence of Charcot foot in the diabetes population stands between 0.1% and 0.4% but rises up to 35% among diabetics who have developed advanced peripheral neuropathy [4,10,11]. Indeed, the latter is related to the diabetic foot due to the consequent alterations of sensitivity, motility, and autonomic processes of the anatomical foot structures [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a Charcot joint increases the risk of diabetic foot ulcer development and subsequent lower limb amputation 17. A diagnosis of Charcot arthropathy in patients with diabetes may reduce life expectancy by on average 14 years, and almost 20% of patients will die within 2 years of diagnosis 18. Early detection of a Charcot foot is therefore essential to reduce the risk of deformity, reduce the risk of foot ulceration and the risk of lower limb amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Em todos os estágios da gestação (no pré-natal, perinatal e pós-parto), apontase alguns fatores prováveis como genética, infecção intrauterina, parto prematuro, baixo peso ao nascer, hipóxia, isquemia perinatal, dessa forma, a PC se caracteriza como um distúrbio cerebral multifatorial, sem uma causa específica identificada (FERREIRA, 2020).…”
Section: Descritoresunclassified